Distal radius fractures result in alterations in scapular kinematics: A three-dimensional motion analysis. Issue 3 (March 2015) - Ayhan, Cigdem; Turgut, Elif; Baltaci, Gul
Abstract Background Scapular motion is closely integrated with arm motion. Injury to a distal segment requires compensatory changes in the proximal segments leading to alterations in scapular motion. Since the effects of distal injuries on scapular kinematics remain unknown, in the present study we investigated the influences on scapular motion in patients with distal injuries. Methods Sixteen subjects with a history of distal radius fracture and 20 asymptomatic healthy subjects (controls) participated in the study. Three-dimensional scapular and humeral kinematic data were collected on all 3 planes of shoulder elevation: frontal, sagittal, and scapular. All testing was performed in a single session; therefore, the sensors remained attached to the participants for all testing. The position and orientation data of the scapula at 30°, 60°, 90°, and 120° humerothoracic elevation and 120°, 90°, 60°, and 30° lowering were used for statistical comparisons. Independent samples t-test was used to compare the scapular internal/external rotation, upward/downward rotation, and anterior/posterior tilt between the affected side of subjects with a distal radius fracture and the dominant side of asymptomatic subjects at the same stage of humerothoracic elevation. Findings Scapular internal rotation was significantly increased at 30° elevation (P = 0.01), 90° elevation (P = 0.03), and 30° lowering (P = 0.03), and upward rotation was increased at 30° and 60° elevation (P < 0.001) on the affected side during frontal plane elevation. Scapular upward rotation and anterior tilt were significantly increased during 30° lowering on both the scapular (P = 0.002 and 0.02, respectively) and sagittal planes (P = 0.01 and 0.02. respectively). Interpretation Patients with distal radius fractures exhibit altered scapular kinematics, which may further contribute to the development of secondary musculoskeletal pathologies.